Using IUCN protected areas management categories as a tool to assess youth preferences for local management of an Important Plant Area (IPA) in Lebanon. (December 2020) - Salman, M.M.; Kharroubi, S.; Itani, M.; Talhouk, S.N.
Highlights: We developed a simple IUCN's PA management categories tool to assess youth's preferences for conservation of an IPA. The majority of youth preferred to manage the IPA near their villages as a "National Park". Environmental profile did not play a role in determining conservation preferences in youth. Abstract: Important Plant Areas (IPAs) designated for their biodiversity value are not always officially protected and often fall within mixed private-public land ownership schemes. The objective of this study was to develop a quantitative tool based on the Protected Area (PA) management categories developed by the International Union for the Conservation of Nature (IUCN) to assess local youth's preferences for conservation of an IPA in Lebanon. A total of 778 high school students living in ten villages that overlap the case study IPA filled the survey. The findings suggest that the youth preferred flexible conservation measures that entail sustainable resource use, education and tourism, and open access. The majority (84 %) preferred National Parks (Protected Area Category II) as the conservation management approach for the site. Participants' environmental attitude, frequency of contact with nature, and self-reported ecological behavior revealed that they have a strong environmental attitude towards nature (96 %) and positive ecological behavior (92 %) after recoding the variables into negative, neutral and positive responses. Moreover, type of school (public or private), gender, age, environmental attitude and frequency of contact predicted 37.2 % of self-reported ecological behavior scores, with environmental attitude as the largest predictor (β (.499), p = .02), The developed tool can serve as a guide to participatory conservation initiatives and local planning of unprotected biodiversity-rich areas, such as IPAs.